O efeito das mudanças históricas de uso do solo sobre as comunidades de aves em uma área urbana no Cerrado - BIANCA BECKER KERBER (2022)
Changes in landscape structure can have short, medium and long-term effects on community structure. However, due to the lack of temporal data, long-term impacts are generally investigated less frequently than short-term impacts. In urban areas, a debt of extinction is expected for many taxonomic groups, due to the conversion of natural ecosystems into anthropized areas. In the present study, we evaluated whether the richness and dissimilarity of bird assemblages in the city of Campo Grande, Mato Grosso do Sul, are explained by the composition of the current landscape, by the composition of the landscape in the past, or by a combination of the composition of the landscape in the past and in the present. We sampled birds in 61 hexagons of 16 ha, in the months of February to March in 2016. In addition, we measured the percentage of native forest and urban infrastructure for three different periods (1985, 2000 and 2016). We found a total of 6151 individuals of 120 bird species in the 61 hexagons sampled. While bird species richness was explained by the percentage of urban areas in 2000, species dissimilarity was explained by the combination of the percentage of native forest in 2000 and the percentage of urban infrastructure in 2016. Our results suggest that there is possibly an extinction debt to be paid in the city, and that areas with greater amounts of forest are more dissimilar to urban areas. The protection and restoration of areas with native vegetation cover may prevent the payment of this debt in the city of Campo Grande.